School and kindergarten attendance and home schooling of pediatric cancer patients before and during the SARS-CoV-2 pandemic: results of a survey of the German Society for Pediatric Oncology and Hematology - Simon, Arne; Siebald, Benjamin; Stamm, Walther; Graf, Norbert; Meier, Stephan; Schrappe, Martin; Groll, Andreas H.; Laws, Hans-Jürgen; Lehrnbecher, Thomas (German Medical Science GMS Publishing House, 2021)
In this multicenter survey (July 07 to August 08, 2020) in pediatric oncology centers (POCs) belonging to the German Society for Pediatric Oncology and Hematology (GPOH), 36 POCs participated (response rate 70.6%). Home schooling practice was judged as satisfying by 79% prior to and by 38% during the pandemic (=0.0007). The individual risk of a SARS-CoV-2 infection and the risk of transmission to other patients/caregivers were arguments against attendance. Most POCs recommended regular social participation/school attendance after the end of intensive therapy. 81% stated that persisting restrictions result in serious negative psychosocial consequences for the patients and their families. In-hospital school education, home schooling and re-attendance of school and kindergarten among pediatric cancer patients have suffered a severe setback during the SARS-CoV-2 pandemic. Continuous communication and education concerning protective measures as well as an individual risk assessment are required to avoid the detrimental exclusion of pediatric oncology patients from kindergarten and school.